Optimization of sugar free dark chocolate product compatible for ketogenic diet and investigating its physicochemical, textural, thermal and sensory properties - Amineh Avami; Mostafa Mazaheritehrani; M. Mohebbi; Fathema Pourhaji (مجله پژوهش‌های علوم و صنایع غذایی ایران, 2023)
There is a challenge in producing a portion both compatible to ketogenic diet and sufficient satiety. This study investigated the possibility of producing sugar-free chocolate product using increasing total fat and protein. The ingredients were chosen such that they do not contain any source of starch and sucrose. The cocoa powder was replaced with cocoa butter substitute (CBS) and sodium caseinate at different levels (0, 5 and 10%) along with constant amount of stevia ketogenic powder and soybean hull as sugar substitute. Results showed that cocoa powder substitution significantly (p< 0.05) led to an increase in moisture, water activity, fat and protein and a decrease in ash and carbohydrate amount, respectively. It was also observed that addition of sodium caseinate and CBS made the chocolate softer and to be easily melted (p< 0.05). Sensory analysis showed that samples with high protein and fat content got better scores in overall acceptance (p< 0.05). Also, principle component analysis showed that the first two components could explain about 81% of total variance. Finally, the best composition was determined by considering both TPA, DSC and sensory properties. This sample contained 5% sodium caseinate and 35% CBS. Moreover, total sugar content and calorie amount of this sample was 2.17% and 547.41 kcal, respectively. The peroxide value of optimized sample was 0.5 meq per kg immediately after production and it reached to 1.13 meq per kg after two months. Consuming 100 g of this chocolate can supply 27% of daily calorie of an adult person (assuming 2000 kcal per day for adults). Consuming this 100 g can also supply 17% and 40% of classic and atkins keto diet. These results showed that, the selected sample with 35% CBS and 5% sodium caseinate could be compatible to ketogenic diet but more clinical research should be done in future.